2008
DOI: 10.1097/ajp.0b013e3181773b69
|View full text |Cite
|
Sign up to set email alerts
|

Parent/Nurse-controlled Analgesia for Children With Developmental Delay

Abstract: Pain scores, side effects, and adverse events suggest that PNCA may be an effective method of pain control for children with developmental delay. Diligent monitoring and education are crucial to ensure safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 20 publications
2
30
0
Order By: Relevance
“…4 Others have since reported on the safety and efficacy of this technique in specific patient groups. 58 More recently, we demonstrated that the rate of complications of PCA by proxy remains low at our institution despite a 4-fold increase in its use. 10 Here we compare the rate of complications in PCA by parent proxy, PCA by clinician (nurse) proxy PCA, and standard (self-administered) PCA to examine the safety of PCA when parents are given authorization to provide doses.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…4 Others have since reported on the safety and efficacy of this technique in specific patient groups. 58 More recently, we demonstrated that the rate of complications of PCA by proxy remains low at our institution despite a 4-fold increase in its use. 10 Here we compare the rate of complications in PCA by parent proxy, PCA by clinician (nurse) proxy PCA, and standard (self-administered) PCA to examine the safety of PCA when parents are given authorization to provide doses.…”
Section: Introductionmentioning
confidence: 76%
“…Even the frequency of naloxone administration cannot be directly compared, as some groups report these data per patient and others report it per treatment day. 4,5,7 Further, it must be kept in mind that the selection of standard PCA vs. clinician-proxy PCA vs. parent-proxy PCA is not randomized, and thus selection bias is a confounding factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been a number of studies evaluating the safety and the side effects of different opioid infusion techniques in children (3–7), but few have quantified the risks in terms of severity. In a recent retrospective study of 302 opioid naïve children receiving PCA by proxy (PCA‐P) vs PCA, clinically significant adverse effects occurred in 22% and 24% of PCA‐P and PCA groups respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The lesser use of the PCA pump might be explained by the difficulty in explaining its concepts to intellectually disabled children. Czarnecki et al have evaluated the safety of postoperative parent/nurse‐controlled analgesia (PNCA) in 71 intellectually disabled children (mean age 10 years) [Czarnecki et al, 2008]. Two patients needed naloxone administration because of respiratory depression or sedation.…”
Section: Pain Treatmentmentioning
confidence: 99%